Determinants of Fraudulent Behavior Tendencies in Local Government - Bunga Ega Oktora; Fadli Fadli; Nurna Aziza (UNIVED Press, 2026)
This study aims to analyze the influence of elements of Fraud Hexagon Theory, namely pressure (stimulus), capability, opportunity, rationalization, arrogance (ego), and collusion on the tendency of fraudulent behavior in the State Civil Apparatus (ASN) of the Kepahiang Regency Government. The research uses a quantitative method with a purposive sampling technique. The research sample amounted to 83 ASNs who met the criteria for positions and a minimum working period of two years. Data were collected through questionnaires and analyzed using multiple linear regression with the help of SPSS. The results of the study show that pressure, arrogance (ego), and collusion have a significant positive effect on the tendency of fraudulent behavior. Capability has a significant negative effect, while opportunity and rationalization have no significant effect. This research proves that Fraud Hexagon Theory is relevant to the public sector and provides implications for strengthening internal control and anti-corruption culture in local governments.